Amar o próximo como a ti mesmo: um estudo do fenômeno da migração a partir da experiência venezuelana - Owino, Kennedy Oduor (2025)
In both the Old and New Testament, we are called to the commandment of love of our neighbour. In his epistle, St John criticizes people who prefer to love only God and disconnect themselves from their neighbor. For him, the love of God is made concrete through the love of our neighbour. The aim of this work is to show who my neighbour is in today's world. From the parable of the Good Samaritan, we can see that our neighbour is the one to whom we approach or the one to whom we show mercy, and this is none other than the migrants and refugees fleeing wars, persecution, natural disasters and poverty, who knock at our doors in search of shelter. The methodology used is based on bibliographical research, which allows us to analyze the commandment of love of our neighbor based on the commandment of love of God, and to make us aware of who really is my neigbour. It was observed that we still have many wounded Venezuelan migrants who are affected by the economic and political crisis, but many of us pass by and move on because of the culture of indifference that manifests itself in the way we treat them. However, they show that the poor are active subjects of the mission and life of the Church